Contrasting effects from a single major histocompatibility complex class II molecule (H-2E) in recovery from Friend virus leukemia. - Perry, L L (1994)
Resistance to erythroleukemia induced by infection with the Friend virus complex (FV) has been mapped to several genes residing both within and outside the murine major histocompatibility complex (MHC). MHC genes located in the A, D, and Qa/Tla regions of the murine H-2 complex have been shown to affect disease resistance through their capacity to regulate various aspects of the host immune response to viral antigens. This study establishes H-2E as the fourth MHC locus controlling immunological resistance to FV. Our investigation into the role of H-2E molecules revealed two distinct and opposite effects on recovery from Friend disease. H-2b/b mice normally lack a functional E gene product and are resistant to high doses of FV. The expression of H-2E molecules in H-2 recombinant or transgenic mice of this genotype resulted in a significant decrease in spontaneous recovery from FV-induced leukemia. In contrast, H-2E expression also appeared to influence recovery from Friend disease in a positive manner, since blocking these molecules with anti-E antibodies in vivo significantly decreased recovery from Friend disease. The data indicate that the positive effects of H-2E molecules derive from their function as restriction elements for helper T-cell recognition of the viral envelope glycoprotein, and we postulate that the negative effects are due to H-2E-dependent deletion in the T-cell repertoire during development.